Effects of Febrile Convulsion Care Program on Knowledge and Perceived Self-efficacy to Care for Children with Febrile Convulsion among Caregivers - Dechthit, Phongthep; Patoomwan, Autchareeya; Phumonsakul, Srisamorn (Nursing Research and Innovation Journal, 2021)
This experimental study with the two-group pretest-posttest research design aimed to examine the effects of the Febrile Convulsion Care Program on knowledge and perceived self-efficacy among primary caregivers of children aged 3 months to 5 years who had a febrile convulsion. The participants consisted of 34 caregivers recruited by purposive sampling from an emergency department and divided into the control and experimental groups equally (17 each). The data were collected from July 2016 to April 2017. The program was developed using Bandura’s Self-Efficacy Theory as a conceptual framework. The instruments used in this study consisted of the Personal Profile Questionnaire, the Knowledge of Febrile Convulsion Questionnaire, and the Perceived Self-efficacy Questionnaire. The data were analyzed using descriptive statistics, Chi-square, and independent t-test. The results demonstrated that the experimental group had a significantly higher mean score of knowledge and perceived self-efficacy than the control group did after two weeks of study. The program developed in this study is useful for nurses to enhance knowledge and perceived self-efficacy among caregivers of children with febrile convulsion receiving care at the emergency department. Keywords: Caregiver, Febrile convulsion, Febrile Convulsion Care Program, Knowledge, Perceived self-efficacy